Financial conditions indexes - David Mayes; Matti Virén (Bank of Finland, 2001)
This paper provides an exposition of the nature, means of estimation and uses of Financial Conditions Indexes (FCIs) and their relationship to the more common Monetary Conditions Indexes (MCIs) that are used by market analysts, international organisations and central banks.Using panel datasets for Western Europe we explore how asset prices, particularly house and stock prices, can provide useful additional indicators of future changes in output and inflation.We find a clear role for house prices but a poorly determined relationship for stock prices.Unfortunately the most useful role for FCIs comes from their incorporation of high frequency data and the opportunity this gives for extracting information about changes in market expectations for inflation and output.This helps market participants make judgements about likely central bank reactions and helps central banks assess the stance of policy between forecasts.While stock prices are high frequency, house prices are not.At quarterly frequency central banks in particular will want to use traditional economic forecasting methods and summary indicators like FCIs will have only a limited role.We illustrate how such an FCI can be used, drawing on monthly data for Finland.
URN:NBN:fi:bof-20140807298
Keywords: 330; financial conditions; asset prices; house prices; stock prices